2010
DOI: 10.1111/j.1349-7006.2010.01667.x
|View full text |Cite
|
Sign up to set email alerts
|

Hsa‐mir‐27a genetic variant contributes to gastric cancer susceptibility through affecting miR‐27a and target gene expression

Abstract: Aberrant microRNA (miRNA) expression is presently proposed to correlate with various human cancers and common single-nucleotide polymorphisms (SNP) at miRNA genes can influence the maturation of miRNAs or miRNA-mediated transcriptional regulation. However, whether miRNAs SNP alter gastric cancer susceptibility is still unclear. Here we investigated the possible role of a common A/G polymorphism (rs895819) within hsa-mir-27a in the development or progression of gastric cancer, and assessed the effect of rs89581… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
128
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 149 publications
(132 citation statements)
references
References 35 publications
3
128
1
Order By: Relevance
“…Similar to other malignancies, the mechanism of gastric carcinogenesis involves a complex multi-stage and multi-factorial process that depends on gene-environment interactions (4). In previous epidemiological studies, genetic factors were demonstrated to play an important role in the development of gastric cancer (5)(6)(7)(8).…”
Section: Introductionmentioning
confidence: 99%
“…Similar to other malignancies, the mechanism of gastric carcinogenesis involves a complex multi-stage and multi-factorial process that depends on gene-environment interactions (4). In previous epidemiological studies, genetic factors were demonstrated to play an important role in the development of gastric cancer (5)(6)(7)(8).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, many features of previously mentioned syndromes (i.e., chromosomal instability, cancer) can be explained by problems associated to chromosome segrega- tion and mitosis, which might result from improper p44 downregulation. In that regard, the overexpression of miR-27a in several cancer types has been proposed to promote oncogenic features, supporting that improper transcriptional shutdown/ inefficient DNA repair might lead to improper resolution of mitosis and cancer (32,(35)(36)(37).…”
Section: Discussionmentioning
confidence: 99%
“…In total, four studies fulfilled the inclusion criteria (Yang et al, 2010;Sun et al, 2010;Zhang et al, 2012;Catucci et al 2012) with 2763 cases and 3556 controls for hsa-mir-27a rs895819 polymorphism. The studies identified and their main characteristics are summarized in Table 1.…”
Section: Characteristics Of Studiesmentioning
confidence: 99%
“…The studies identified and their main characteristics are summarized in Table 1. Among these publications, there were two studies of European descent (Yang et al, 2010;Zhang et al, 2012), two study of Asian descent (Sun et al, 2010;Catucci et al, 2012). All of the cases were histologically confirmed as breast cancer or Gastric cancer.…”
Section: Characteristics Of Studiesmentioning
confidence: 99%